Digitalization Training for Karang Taruna to Enhance the Capacity for Information Management and Social Media of Youth Organizations in Barru Regency - Muh. Syilfa Nooviar; Faisal Ardiansyah; Misbahuddin M; Andi Rahmat Nizar Hidayat; Hidayat Muhammad (Yayasan Daarul Huda Kruengmane, 2026)
Youth organizations such as Karang Taruna play an important role in community empowerment, social development, and youth participation in local governance. However, many youth organizations still face challenges in utilizing digital technology to support organizational communication and information management. This community service program aims to improve the capacity of Karang Taruna members in Barru Regency in managing digital information and utilizing social media platforms for organizational communication. The program employed participatory training methods consisting of lectures, demonstrations, hands-on practice, and group discussions. Participants were introduced to digital communication strategies, social media content management, and online information dissemination techniques.The results show that participants experienced an improvement in their understanding of digital communication strategies and practical skills in managing social media platforms. Participants were able to create organizational content, publish activity reports, and develop communication strategies using social media platforms. The program also strengthened participants’ awareness of the importance of digital presence for youth organizations. Therefore, digitalization training can enhance the organizational capacity of youth groups in disseminating information, strengthening community engagement, and supporting social development initiatives.